MEMBANDINGKAN KINERJA MESIN BENSIN DUA LANGKAH SATU SILINDER PADA SEPEDA MOTOR MENGGUNAKAN VARIASI CAMPURAN BAHAN BAKAR MINYAK HASIL PROSES PIROLISIS SAMPAH PLASTIK DAN PREMIUM DENGAN PREMIUM MURNI - Wardoyo Wardoyo (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2016)
This research was aimed to know the performance of engine using variation of plastic waste pyrolysis and premium process result-gasoline fuel mix and pure premium and comparing with pure premium. The fuel mix variation used consisted of 20% plastic waste pyrolysis process result oil, 80% premium and 49%plastic waste pyrolysis process result oil, 60%premium. The research procedures included firstly the tested engine given pure premium fuel and the engine was run for 2-3 minutes by installing a transmission gear in 4th position, then rotation, torsion, power and specific fuel consumption was measured. Furthermore, the engine was stopped and the fuel was substituted with varied plastic waste pyrolysis process result oil mix, the engine was re-run. The measurement rotations, torsion, power and specific fuel construction was conducted by the same way with pure premium fuel testing. Out of test results for the same rotation of 5000-8000 engine RPM using fuel mix of 20% plastic waste pyrolysis process result oil the average power was 10.04 HP, average torsion of 11.10 Nm, specific fuel consumption of 0.100 kg/hour HP and engine using fuel mix of 40% plastic waste pyrolysis process result oil the average power was 9.7 HP, average torsion of 10.82 NM, specific fuel consumption o f 0.068 kg/hour HP. While using pure premium the average power was 9.8 HP, average torsion of 10.94 Nm, specific fuel consumption was 0.103 kg/hour HP. If compared, so that engine performance using fuel mix of 40% plastic waste pyrolysis process result oil and 60% premium almost approached engine performance using pure premium fuel and actually 20% fuel mix of plastic waste pyrolysis process result oil and 80% premium was better.